Current Insights into the Potential Misuse of Platelet-based Applications for Doping in Sports - Scully, David; Matsakas, Antonios (International Journal of Sports Medicine, 2019)
Platelet-based applications are currently used for the delivery of growth factors and other biomolecules as autologous biomaterials in regenerative medicine and cosmetic therapies. Many studies have revealed that platelet-based applications such as platelet-rich plasma and platelet releasate exhibit beneficial biological effects after a sports injury or trauma when administered locally by intramuscular injections. At present, treatment of the public, patients and athletes with platelet-based applications is permitted and regulated by the Food and Drug Administration and the World Anti-Doping Agency. Since 2011 the use of autologous platelet-rich plasma is permitted in competitive sports by the World Anti-Doping Agency, due to the lack of evidence in performance enhancement and anabolic effects. However, accumulating research has recently shed light on the role of platelet-derived growth factors in wound healing, skeletal myogenesis, muscle stem cell function and tissue regeneration. Although any ergogenic potential of platelet-rich plasma and platelet releasate on intact skeletal muscle and human sports performance remain to be established, novel evidence suggests that platelet-derived growth factors can modulate muscle, tendon, ligament, protein synthesis/degradation, vascularization, energy utilization and regenerative capacity in various experimental settings. Since platelet-based applications are currently not prohibited, they constitute a tool for potential abuse and doping in sports. The aim of this review is to critically discuss and assimilate current insights and biological evidence that set the ground for exploitation and misuse in competitive sports, and develop strategies to combat these activities.
Keywords: platelet-rich plasma; world anti-doping agency; prohibition list; growth factors; sports injury